Fine-Scale Population Admixture Landscape of Tai–Kadai-Speaking Maonan in Southwest China Inferred From Genome-Wide SNP Data - Chen, Jing; He, Guanglin; Ren, Zheng; Wang, Qiyan; Liu, Yubo; Zhang, Hongling; Yang, Meiqing; Zhang, Han; Ji, Jingyan; Zhao, Jing; Guo, Jianxin; Chen, Jinwen; et al. (Frontiers in Genetics, 2022)
Guizhou province harbours extensive ethnolinguistic and cultural diversity with Sino-Tibetan-, Hmong-Mien- and Tai-Kadai-speaking populations. However, previous genetic analyses mainly focused on the genetic admixture history of the former two linguistic groups. The admixture history of Tai-Kadai-speaking populations in Guizhou needed to be further characterised. Thus, we genotyped genome-wide SNP data from 41 Tai-Kadai-speaking Maonan people and made a comprehensive population genetic analysis to explore their genetic origin and admixture history based on the pattern of the sharing alleles and haplotypes. We found a genetic affinity among geographically different Tai-Kadai-speaking populations, especially for Guizhou Maonan people and reference Maonan from Guangxi. Furthermore, formal tests based on the f3/f4-statistics further identified an adjacent connection between Maonan and geographically adjacent Hmong-Mien and Sino-Tibetan people, which was consistent with their historically documented shared material culture (Zhang et al., 2020). Fitted qpAdm-based two-way admixture models with ancestral sources from northern and southern East Asians demonstrated that Maonan people were an admixed population with primary ancestry related to Guangxi historical people and a minor proportion of ancestry from northern East Asians, consistent with the linguistically supported their southern China origin. Here we presented the landscape of genetic structure and diversity of Maonan people and a simple demographic model for their evolutionary process. Further whole-genome-sequence-based projects can be presented with more detailed information about the population history and adaptative history of the Guizhou Maonan people.